EVALUATION OF THE DEVELOPMENT OF THE SUKOWATI EMAS PROGRAM ACHIEVEMENT AT THE INDONESIAN NATIONAL SPORTS COMMITTEE, SRAGEN REGENCY - Umayah, Vensa Lukita; Nasuka, Nasuka; Irawan, Fajar Awang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
PROSUKMA is a special program created by KONI Sragen Regency. This study aims to evaluate the antecedent which includes the background, and planning of coaching programs, evaluating transactions which include recruitment of trainers, athlete recruitment, training programs, supporting facilities and infrastructure, funding, coordination, and welfare of KONI PROSUKMA Sragen development, and evaluating outcomes which include the successful implementation of coaching in the achievement of fostering KONI PROSUKMA Sragen. This study uses a descriptive qualitative approach with the Countenance evaluation model from Robert E. Stake. The subjects in this study were administrators, trainers, and athletes KONI PROSUKMA Sragen Regency. The results of this study are the antecedent evaluation consisting of the background and planning of the KONI PROSUKMA development program, Sragen Regency is clear and well organized, transaction evaluation consisting of recruiting coaches and athletes has been going well, the implementation of the training program is quite proper following the training program the schedule, facilities, and infrastructure are not good enough, some have not been of a national standard, funding is going well enough not enough to meet the needs of coaching, coordination is going well, the welfare provided for trainers, and athletes is quite good, but not yet optimal, and evaluating outcomes in the form of athlete achievement in some sports it is quite good but not stable. There are still sports that have not yet achieved accomplishments.